Wash Day Blues to Depart - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet discusses methods for improving one's laundry room. Provides decorating tips and advises acquiring laundry appliances such as electrical washers, clothes dryers, flat plate ironers, and a radio for listening to music while laundering. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Interior decoration; Paint materials; Household appliances; Laundry--Equipment and supplies; Varnish industry; Paint industry and trade; Advertising--Paint